Pengaruh Kegiatan Ekstrakurikuler Pramuka Terhadap Motivasi Siswa SD Negeri 1 Selanegara (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to find out whether there is an influence of scout extracurricular activities on the motivation of SD Negeri 1 Selanegara students. This study uses a quantitative type with a survey method. The subjects of this study are students in grades III, IV, and V of SD Negeri 1 in the country totaling 25 students with simple random selection or using the Simple Random Sampling method. Data collection uses questionnaires, interviews, observations, and documentation. The student motivation questionnaire used was 33 statements that were declared valid and reliable. The results of the study showed an increase in student motivation in scouting extracurricular activities with 95% declared good and 5% adequate. The results of the Shapiro-Wilk Test can be seen that the significance value of variable X (Student Motivation) is 0.128 and variable Y (Scout Extracurricular) is 0.652 which means that the significance value of > 0.05, then it can be concluded that both data are normally distributed. The results of the linearity test showed that the two variables had a linear relationship of 0.948 more than 0.05 with Deviation From Linearity. The results of the T test are known to have a significance value of SIG.< 0.05. The value of t is 4.542 and t of the table is 2.069 which means that t is calculated > t of the table and the value of R Square is 0.473. So it can be concluded that Ha was accepted, which means that there is an influence of scout extracurricular activities on the motivation of SD Negeri 1 Selanegara students.